Distinct genetic variation of Helicobacter pylori cagA, vacA, oipA, and sabA Genes in Thai and Korean dyspeptic patients - Wongwarut Boonyanugomol (2019)
© 2018, The Korean Society for Microbiology and Biotechnology. Differences in host ethnicities and geographical distributions may influence the genetic variation and pathogenesis of Helicobacter pylori strains, particularly with respect to those with a high risk of gastric cancer and in Asian Enigma regions. We simultaneously identified H. pylori virulence-associated genes involved in inflammation and cell damage in Thai and Korean dyspeptic patients. The virulence-associated gene cagA, cagA genotypes (East Asian and Western type cagA), vacA genotypes (s- and m-), oipA, and sabA were detected in Thai and Korean dyspeptic patients by polymerase chain reaction (PCR), real-time PCR, and DNA sequence analysis. Comparisons between the two regions showed that cagA, East Asian type cagA, and vacA s1/m1 in Korean dyspeptic patients occurred at rates of 100%, 86.67%, and 88.89%, respectively (p < 0.05). The oipA- and sabA-positive samples were significantly more predominant in the Korean population (95.56%, 91.11%) than in the Thai population (32%, 34%). DNA sequence analysis revealed differences in the patterns of cytosine-thymine dinucleotide repeats of oipA and sabA among the two populations of dyspeptic patients. Our results indicate that the H. pylori strains detected in the two regions were divergent, and strains colonizing the Korean dyspeptic patients may be more virulent than those in the Thai population. Our data may help explain H. pylori pathogenesis in Asian Enigma areas with a low gastric cancer incidence. However, other factors involving H. pylori infection in these two regions should be further analyzed.